Big buses in a small country: The prospects for bus services in Wales. (November 2016) - Preston, John
Abstract: The evolution of the bus market and industry in Wales since deregulation in the mid-1980s is reviewed. After a brief period of competition, which seemed to offer the prospect of welfare gains, the industry rapidly consolidated, with resulting losses in bus usage and welfare, similar to the rest of Great Britain outside London. There were large increases in subsidy following the introduction of a national free concessionary fares scheme in 2002. There is some evidence that some of this subsidy has leaked, at least some of the time, into super-normal profits, in part due to generous concessionary fare reimbursement terms. For the urban parts of Wales, particularly in the North East (centred on Wrexham) and the South East (centred on Cardiff), there are aspirations to develop Bus Rapid Transit to supplement the existing rail network. For rural Wales, there have been long standing aspirations to develop more flexible public transport services and long distance bus services, but this has often been thwarted by lack of funding. Organisational reforms that might assist the Welsh Government in delivering these aspirations are reviewed, including Quality Contracts, Quality Partnerships and Community Partnerships.